Reduction of the hydraulic retention time at constant high organic loading rate to reach the microbial limits of anaerobic digestion in various reactor systems. (October 2016) - Ziganshin, Ayrat M.; Schmidt, Thomas; Lv, Zuopeng; Liebetrau, Jan; Richnow, Hans Hermann; Kleinsteuber, Sabine; Nikolausz, Marcell
Highlights: Anaerobic digestion at extreme short HRT was investigated in various reactors. Functional markers for H2 and CH4 producing pathways were analyzed on mRNA level. Stable isotope analysis of the biogas was applied to assess methanogenic pathways. Depending on HRT Clostridiales and Spirochaetales were the most active in reactors. Increased activity of Methanosaeta was found during HRT decrease in CSTR and ASBR. Abstract: The effects of hydraulic retention time (HRT) reduction at constant high organic loading rate on the activity of hydrogen-producing bacteria and methanogens were investigated in reactors digesting thin stillage. Stable isotope fingerprinting was additionally applied to assess methanogenic pathways. Based on hydA gene transcripts, Clostridiales was the most active hydrogen-producing order in continuous stirred tank reactor (CSTR), fixed-bed reactor (FBR) and anaerobic sequencing batch reactor (ASBR), but shorter HRT stimulated the activity of Spirochaetales . Further decreasing HRT diminished Spirochaetales activity in systems with biomass retention. Based on mcrA gene transcripts, Methanoculleus and Methanosarcina were the predominantly active in CSTR and ASBR, whereas Methanosaeta and Methanospirillum activity was more significant in stably performing FBR. Isotope values indicated the predominance of aceticlastic pathway in FBR. Interestingly, an increased activity of Methanosaeta was observed during shortening HRT in CSTR and ASBR despite high organic acids concentrations, what was supported by stable isotope data.